Which expression gives the distance between the points (-3, 4) and (6, -2)?
![Which expression gives the distance between the points 3 4 and 6 2 class=](https://us-static.z-dn.net/files/d60/36e678df9c1240a9479f3cc5454c9a82.png)
For this case we have that by definition, the distance between two points is given by:
[tex]d = \sqrt {(x_ {2} -x_ {1}) ^ 2+ (y_ {2} -y_ {1}) ^ 2}[/tex]
We have the following points:
[tex](x_ {1}, y_ {1}) = (6, -2)\\(x_ {2}, y_ {2}) = (- 3,4)[/tex]
Substituting we have:
[tex]d = \sqrt {(- 3-6) ^ 2 + (4 - (- 2)) ^ 2}\\d = \sqrt {(- 3-6) ^ 2 + (4 + 2) ^ 2}[/tex]
Answer:
Option B